Neural crest cell-derived pericytes act as pro-angiogenic cells in human neocortex development and gliomas - Girolamo, Francesco (Fluids Barriers CNS, 2021)
Central nervous system diseases involving the parenchymal microvessels are frequently associated with a ‘microvasculopathy’, which includes different levels of neurovascular unit (NVU) dysfunction, including blood–brain barrier alterations. To contribute to the understanding of NVU responses to pathological noxae, we have focused on one of its cellular components, the microvascular pericytes, highlighting unique features of brain pericytes with the aid of the analyses carried out during vascularization of human developing neocortex and in human gliomas. Thanks to their position, centred within the endothelial/glial partition of the vessel basal lamina and therefore inserted between endothelial cells and the perivascular and vessel-associated components (astrocytes, oligodendrocyte precursor cells (OPCs)/NG2-glia, microglia, macrophages, nerve terminals), pericytes fulfil a central role within the microvessel NVU. Indeed, at this critical site, pericytes have a number of direct and extracellular matrix molecule- and soluble factor-mediated functions, displaying marked phenotypical and functional heterogeneity and carrying out multitasking services. This pericytes heterogeneity is primarily linked to their position in specific tissue and organ microenvironments and, most importantly, to their ontogeny. During ontogenesis, pericyte subtypes belong to two main embryonic germ layers, mesoderm and (neuro)ectoderm, and are therefore expected to be found in organs ontogenetically different, nonetheless, pericytes of different origin may converge and colonize neighbouring areas of the same organ/apparatus. Here, we provide a brief overview of the unusual roles played by forebrain pericytes in the processes of angiogenesis and barriergenesis by virtue of their origin from midbrain neural crest stem cells. A better knowledge of the ontogenetic subpopulations may support the understanding of specific interactions and mechanisms involved in pericyte function/dysfunction, including normal and pathological angiogenesis, thereby offering an alternative perspective on cell subtype-specific therapeutic approaches. [Image: see text]